The effect of green tea on blood pressure and lipid profile: a systematic review and meta-analysis of randomized clinical trials. - Onakpoya, I; Spencer, E; Heneghan, C; Thompson, M (2014)
INTRODUCTION: Many different dietary supplements are currently marketed for the management of hypertension, but the evidence for effectiveness is mixed. The aim of this systematic review was to evaluate the evidence for or against the effectiveness of green tea (Camellia sinensis) on blood pressure and lipid parameters. METHODS AND RESULTS: Electronic searches were conducted in Medline, Embase, Amed, Cinahl and the Cochrane Library to identify relevant human randomized clinical trials (RCTs). Hand searches of bibliographies were also conducted. The reporting quality of included studies was assessed using a checklist adapted from the CONSORT Statement. Two reviewers independently determined eligibility, assessed the reporting quality of the included studies, and extracted the data. As many as 474 citations were identified and 20 RCTs comprising 1536 participants were included. There were variations in the designs of the RCTs. A meta-analysis revealed a significant reduction in systolic blood pressure favouring green tea (MD: -1.94 mmHg; 95% CI: -2.95 to -0.93; I(2) = 8%; p = 0.0002). Similar results were also observed for total cholesterol (MD: -0.13 mmol/l; 95% CI: -0.2 to -0.07; I(2) = 8%; p < 0.0001) and LDL cholesterol (MD: -0.19 mmol/l; 95% CI: -0.3 to -0.09; I(2) = 70%; p = 0.0004). Adverse events included rash, elevated blood pressure, and abdominal discomfort. CONCLUSION: Green tea intake results in significant reductions in systolic blood pressure, total cholesterol, and LDL cholesterol. The effect size on systolic blood pressure is small, but the effects on total and LDL cholesterol appear moderate. Longer-term independent clinical trials evaluating the effects of green tea are warranted.